ASPEK-ASPEK KAJIAN PENDIDIKAN ISLAMI DALAM SENI PERTUNJUKAN SALAWAT DULANG - FIRDAUS FIRDAUS; JONNI JONNI; DEBBY TRISMA (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2020)
AbstractSalawat dulang was identic with da’wah of Islam. It has development and changes experience dramatically in performing form or it function, and deeper delivery messages. Performing form identify that player of Salawat Dulang can adapt newest gendre of music to the salawat dulang, inded they not only can adapt that but also they can put intheaterical instrument in Salawat Dulang. Salawat dulang his also crusial function for sending message of education, culture, politic, economic, social, ect by media of communication base on market needs. Salawat Dulang is the most perferable music in whole Minangkabau and the most choosen one in community of Minangkabau. Based on statement on the top, research one to observation education of Islam and element of Salawat Dulang as performance art.